Kinerja Pengeringan Gabah Menggunakan Alat Pengering Tipe Rak dengan Energi Surya, Biomassa, dan Kombinasi - Tamaria Panggabean; Arjuna Neni Triana; Ari Hayati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2017)
Paddy drying was performed using a hybrid drier utilizing solar energy, biomass and combined solar-biomass energy as energy sources. This research objective was to evaluate performance of the hybrid paddy drier using solar energy and paddy straw and coconut coir biomass. The experimental and descriptive method was used. The result showed that the drier with solar system was capable to generate temperature of drying chamber to 40.42 °C in average, while the average relative humidity was 41.45%. The paddys final moisture was 14.88%w.b after 7 hours of drying with drying rate of 0.64% d.b/h and energy consumption of 32,595.32 kJ. Paddy drying with biomass energy system was capable to obtain drying chambers temperature of 33.8 °C in average, the average relative humidity of 57%, the final moisture of 15.57%, the drying rate of 0.50 %d.b/h and energy consumption of 160,662.15 kJ with the same drying times. The solar-biomass drying system was capable to achieve temperature of 39.98 °C, the average relative humidity of 45.85 %, the final moisture of 15.33%w.b with drying rate of 0.55 %d.b/h and energy consumption of 136,457.76 kJ. Therefore, the best performance for drying paddys was with the solar drying system. ABSTRAKPengeringan gabah dapat dilakukan menggunakan alat pengering energi surya, energi biomassa dan energi kombinasi surya dan biomassa. Penelitian ini bertujuan untuk menguji kinerja alat pengering gabah hybrid energi surya dan biomassa jerami padi dan sabut kelapa. Metode yang digunakan dalam penelitian ini adalah metode eksperimental dan deskritif. Hasil penelitian menunjukkan bahwa pengeringan gabah dengan energi surya menghasilkan suhu ruang pengering rata-rata 40,42 °C, kelembaban relatif ruang pengering rata-rata 41,45 %, waktu pengeringan 7 jam, kadar air akhir rata-rata 14,88 %bb, laju pengeringan rata-rata 0,64 %bk/jam, dan energi pengering 32.595,32 kJ. Pengeringan gabah dengan energi biomassa menghasilkan suhu ruang pengering rata-rata 33,8 °C, kelembaban relatif ruang pengering rata-rata 57 %, waktu pengeringan 7 jam, kadar air akhir rata-rata 15,57 %bb, laju pengeringan rata-rata 0,50 %bk/jam, dan energi pengering 160.662,15 kJ. Pengeringan gabah dengan energi kombinasi surya dan biomassa menghasilkan suhu ruang pengering rata-rata 39,98 °C, kelembaban relatif ruang pengering rata-rata 45,85 %, waktu pengeringan 7 jam, kadar air akhir rata-rata 15,33 %, laju pengeringan rata-rata 0,55 %bk/jam, dan energi pengering 136.457,76 kJ. Kinerja yang diperoleh alat pengering terbaik menggunakan energi surya dengan kadar air akhir sebesar 14,88%bb, laju pengeringan 0,64 %bk/jam dan kebutuhan energi pengeringan 32.595,32 kJ.